Early versus delayed administration of granulocyte-colony stimulating factor following chemotherapy in pediatric patients with Ewing sarcoma. (March 2020) - Al-Momani, Deema; Al-Qasem, Wiam; Kasht, Rawan; Sultan, Iyad
Background: The optimal timing of initiating granulocyte-colony stimulating factor following chemotherapy in pediatric patients has not been clearly defined. This study aimed to compare the administration of granulocyte-colony stimulating factor on day 1 versus day 3 postchemotherapy in pediatric patients with Ewing sarcoma. Method: A retrospective study of pediatric patients with Ewing sarcoma who received granulocyte-colony stimulating factor following chemotherapy between January 2016 and September 2018 at a comprehensive cancer center. The institution's chemotherapy protocol for Ewing sarcoma was modified in April 2017 to include granulocyte-colony stimulating factor initiation on day 3 instead of day 1 post-chemotherapy. Febrile neutropenia requiring hospitalization, duration of hospital stay, and chemotherapy delay were compared for patients before and after the protocol change. Results: Over the study period, 250 cycles were evaluated with day 1 granulocyte-colony stimulating factor and 221 cycles with day 3 granulocyte-colony stimulating factor. There were no differences between the day 1 and day 3 groups in the number of cycles associated with Febrile neutropenia requiring hospitalization (34 vs. 19, p = 0.086), and the length of Febrile neutropenia-related hospitalization (mean 4 ± 2.1 vs. 4.6 ± 1.8, p = 0.123). However, delay in chemotherapy due to neutropenia was reported in significantly more cycles in the day 1 group, compared to the day 3 group (37 vs. 16, p = 0.01). Conclusions: Febrile neutropenia resulting in hospital admission and the length of hospital stay was not different between pediatric patients with Ewing sarcoma who received granulocyte-colony stimulating factor on day 1 or day 3 post-chemotherapy. Chemotherapy delay due to neutropenia was higher in patients who received granulocyte-colony stimulating factor on day 1. Larger studies are required to fully determine the impact of delayed initiation of granulocyte-colony stimulating factor.